Purchase Intentions Short Video Reels, Study on Instagram - Nur Rizki Faradia Ananda; Erwin Halim (Budapest International Research and Critics University, 2022)
This research is motivated by the large number of internet users in Indonesia, as well as the use of Instagram with a variety of useful features provided, one of which is the Reels feature. This is also supported by the increasing number of marketers who use social media as part of a place to promote to a wider community without space and time limits, so the features contained in Reels strongly support the activities of these marketers. This research was conducted using quantitative methods with the method of Structural Equiation Modeling (SEM) analysis with SmartPLS 3.0 as data processing software. The purpose of this study is to find out how the influence of the Reel feature on Instagram can have a direct effect on Consumer Buying Interest or it can also be done indirectly through Consumer Brand Attitudes. The sampling technique used is purposive sampling technique. The results of this study indicate that variables based on independent scenarios, user participation, perceived benefits, perceived enjoyment, celebrity involvement directly have a positive and significant effect on consumer brand attitudes, and consumer brand attitudes also have a positive and significant effect on consumer purchase intentions. While interesting content directly (direct effect) does not have a positive and significant effect on consumer brand attitudes.